Effects of anagliptin on plasma glucagon levels and gastric emptying in patients with type 2 diabetes: An exploratory randomized controlled trial versus metformin. (December 2019) - Nakagawa, Tomoko; Nagai, Yoshio; Yamamoto, Yutaro; Miyachi, Atsushi; Hamajima, Hitoshi; Mieno, Eri; Takahashi, Masaki; Inoue, Eisuke; Tanaka, Yasushi
Highlights: Metformin (1000 mg) and anagliptin (200 mg) improved glycemic control similarly. Anagliptin slightly decreased the incremental AUC of plasma glucagon during the meal test. Anagliptin increased early plasma levels of active GLP-1, active GIP and C-peptide. Neither anagliptin nor metformin caused any delay of gastric emptying. Abstract: Aims: Glucagon has an important role in glucose homeostasis. Recently, a new plasma glucagon assay based on liquid chromatography-high resolution mass spectrometry was developed. We evaluated the influence of a dipeptidyl peptidase-4 inhibitor (anagliptin) on plasma glucagon levels in Japanese patients with type 2 diabetes by using this new assay. Methods: Twenty-four patients with type 2 diabetes were enrolled in a prospective, single-center, randomized, open-label study and were randomly allocated to 4 weeks of treatment with metformin (1000 mg/day) or anagliptin (200 mg/day). A liquid test meal labeled with sodium [ 13 C] acetate was ingested before and after the treatment period. Samples of blood and expired air were collected over 3 h. Plasma levels of glucose, glucagon, C-peptide, glucagon-like peptide-1 (GLP-1), and glucose-dependent insulinotropic polypeptide (GIP) were measured, and gastric emptying was also evaluated. Results: Twenty-two patients completed the study (metformin group: n = 10; anagliptin group: n = 12). Glycemic control showed similar improvement in both groups. In the anagliptin group, there was a slight decrease of the incremental area under the plasma concentration versus time curve for glucagon after the test meal ( P = 0.048). In addition, the plasma level of active GLP-1 and GIP was increased, and plasma C-peptide was also increased versus baseline. Neither anagliptin nor metformin delayed gastric emptying. Conclusions: In patients with type 2 diabetes maintained endogenous insulin secretion, anagliptin increased the plasma level of active GLP-1 and GIP in association with a slight stimulation of insulin secretion and slight inhibition of glucagon secretion, but did not delay gastric emptying. Clinical Trial Registry: University hospital Medical Information Network UMIN000028293.